Penyebab Tidak Terlaksananya Prosedur Akuntansi Sistematis Pada Usaha Mikro Kecil dan Menengah - Yustina Alfira Nay; Maria Goreti Malut; Rere Paulina Bibiana (Journal on Education, 2023)
This study aims to analyze the description of financial records that have been used by MSMEs, the causes of not implementing systematic accounting procedures and strategies related to solving financial recording problems. Primary data were obtained from interviews, observations, and documentation of 12 informants. Secondary data were obtained from documentation studies provided by third parties, such as BPS, related agencies, and previous research. Furthermore, researchers performed qualitative data analysis techniques. The results of the study found that SMEs have so far implemented simple financial records. Some of the reasons for not implementing systematic accounting procedures are perception, motivation, financial literacy, and the role of institutions such as universities, public accounting firms, non-governmental organizations, and the government. The theoretical contribution of this research is to add to previous literature regarding the causes of not implementing systematic accounting procedures and appropriate strategies that can be used by MSME actors. The practical contribution is that MSME actors are able to compile systematic financial reports.